Implementasi Kebijakan Merdeka Mandiri Belajar: Studi Kasus Di UPTD SDN Pangilen 3 Sampang - Khusni Alhan; Sari Nusantara Putri (Thawalib: Jurnal Kependidikan Islam, 2023)
The purpose of this research is to find out and describe the implementation of independent learning at Pangilen 3 Sampang Public Elementary School from the point of view of George E Edward III. The research was conducted qualitatively with a case study approach. Data collection techniques: interviews; observation and documentation. Data processing techniques: reduction, data presentation, and conclusion. Data validation techniques: triangulation of sources, techniques, and confirmability. The results of the study show: (1) Communication Factors: (a) transformation, well conveyed. (b) clarity, and understanding of how to implement the policy. (3) consistency, the contents of the policy are not confusing. (2) Resource factors: (a) human: principal: decides the 2013 curriculum face to face. Teacher: independent curriculum learning training. Students: take part in face-to-face learning. Community: supports face-to-face learning. (b) Finance: School Operational Assistance. (c) Equipment: learning media. (d) Information: Minister of National Education and District Education Office. (e) Authorities: District Education Office – supervisor – the school principal – Teacher. (3) Disposition factors: schools accept and implement existing policies. (4) Bureaucratic Structure Factors: school principals - teachers - students.